Advanced structural characterization of energy storage materials - Gupta, Disha (2019)
Lithium-ion batteries are a promising alternative to the already existing lead batteries, as an efficient, inexpensive energy storage option for the ever increasing demand for energy around the world today. Considering the growing concerns over the environmental impacts of non-renewable energy sources, clean and renewable energy sources is a topic of escalating importance. Lithium being the lightest metal, least dense and providing greatest electrochemical potential, has become an integral part of a battery material component. This thesis aims at studying the structural and chemical properties of some energy storage materials as potential Li-ion cathodes in order to overcome the present drawbacks concerning such materials. The materials under study in this research involves LiFePO4 (LFP) and Mn-doped LiFePO4 systems – LiMn0.1Fe0.9PO4 (LMFP 0.1), LiMn0.3Fe0.7PO4 (LMFP 0.3), LiMn0.5Fe0.5PO4 (LMFP 0.5). While initial characterization procedures like X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) have been employed to probe the structure of these materials, the key characterization technique used for the analysis of these battery materials have been done using X-ray Absorption Spectroscopy (XAS) studies. Local electronic and structural changes for LFP, LMFP (0.1-0.5) have been investigated using XAS. For both LFP and LMFPs, the structural comparison has been carried out between two laboratory-synthesized materials using ball milling and flame spray techniques. LFP was also obtained from two commercial sources – Linxi and Targray. Targray LFP showed better electrochemical performance than the Linxi LFP and the XAS studied showed that the structure of Targray LFP matched the literature more closely than the Linxi LFP. The bond length analysis of the Linxi LFP showed much shorter Fe-O bonds than Targray which could hinder the Li-diffusivity and hence affect the performance. The Fe K-edge for both LFPs and LMFPs showed a valence change from 2+ to 3+ while charging and back to 2+ with discharging. Whereas, for low concentrations of Mn, for Mn K-edge showed no valence change. However, with a Fe: Mn ratio of 1:1, partial Mn oxidation was observed. For the first time, the P K-edge XAS was also studied to investigate the electronic structure of all the LMFPs electrodes which showed that de-lithiation of all these materials resulted in the hybridization of Fe 3d and P 3p states. Theoretical simulations for near edge XAS data have also been attempted for recreating the model compounds used as reference compounds for the experimental data. These simulations can help in understanding the evolution of the XANES spectra with the inclusion of higher shells, distortion around the absorbing atom, anti-site disorder etc. Sulphate-based Li-ion battery material, Li2Mn(SO4)2 (LMS) was also studied since the sulphate polyanion (SO4)2- has higher electronegativity compared to (PO4)3- and achieves higher redox potentials through inductive effects. XAS studies were conducted for the first time for the LMS material for both Mn and S K-edges. However, the electrochemical results showed little redox reactivity and the XAS studies showed a very slight change in the structure as well. Therefore, further studies involving X-ray Photoelectron Spectroscopy (XPS) was engaged to study the behaviour of this material which showed a possibility of surface reactions rather than bulk activity.